2022
DOI: 10.3233/ch-211214
|View full text |Cite
|
Sign up to set email alerts
|

Sublingual microcirculatory alterations during the immediate and early postoperative period: A systematic review and meta-analysis

Abstract: BACKGROUND: The incidence of postoperative microcirculatory flow alterations and their effect on outcome have not been studied extensively. OBJECTIVE: This systematic review and meta-analysis was designed to investigate the presence of sublingual microcirculatory flow alterations during the immediate and early postoperative period and their correlation with complications and survival. METHODS: A systematic search of PubMed, Scopus, Embase, PubMed Central, and Google Scholar was conducted for relevant articles … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…In clinical practice, a fluid challenge may increase the stressed volume (and thus Pmca and CO) until a certain point, but may not always improve microcirculatory perfusion. On the other hand, fluid overload increases CVP, which decreases venous return and retrogradely increases post-capillary venular pressure, impairing microcirculatory perfusion [39-41]. The association between the Pmca and Δp ranges in our study (Figure 3) further enhances the potential of Pmca to serve as a hemodynamic coherence monitoring tool.…”
Section: Discussionsupporting
confidence: 59%
“…In clinical practice, a fluid challenge may increase the stressed volume (and thus Pmca and CO) until a certain point, but may not always improve microcirculatory perfusion. On the other hand, fluid overload increases CVP, which decreases venous return and retrogradely increases post-capillary venular pressure, impairing microcirculatory perfusion [39-41]. The association between the Pmca and Δp ranges in our study (Figure 3) further enhances the potential of Pmca to serve as a hemodynamic coherence monitoring tool.…”
Section: Discussionsupporting
confidence: 59%
“…Preoperative CPR levels were not correlated with intraoperative sublingual microcirculation. Our findings suggest that basal inflammatory state, measured by suPAR, synergizes with operative trauma to mediate microvascular dysfunction, which in turn has been suggested to mediate postoperative complications [ 44 ]. The association between the level of preoperative systemic inflammation and intraoperative impairment of sublingual microvascular perfusion may be particularly important during prolonged anesthetic/surgical duration.…”
Section: Discussionmentioning
confidence: 95%
“…In a prospective observational study with 25 patients receiving standard perioperative care following major abdominal surgery, microcirculatory flow impairment was associated with higher rates of postoperative complications [ 48 ]. In addition, a recent systematic review and meta-analysis reported significant sublingual microcirculatory flow alterations during the immediate and early postoperative period [ 44 ]. However, the exact underlying mechanisms between chronic inflammation and microvascular impairment are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations